Enhanced Mechanical Properties in 6082 Aluminum Alloy Processed by Cyclic Deformation - Xuanliang Chen (MDPI AG, 2021)
Aging heat treatment is the most commonly used strengthening method for Al–Mg–Si alloys since high-density precipitates will be formed to hinder the movement of dislocations. In the current work, room temperature cyclic deformation was attempted to strengthen the alloy. We compared tensile test results of aged samples and cyclically deformed samples. It was found that cyclically deformed samples can achieve similar strength and approximately twice the uniform elongation as the peak aged samples. The high density of dislocations and nanoclusters observed in the cyclically deformed samples is thought to be the main reason for strengthening. Different cyclic deformation conditions have been tried and their effects were discussed.